New technologies and creative practices in teaching groupwork - Byrne, Anne; McGovern, Marguerita; Bradley, Ciara (Groupwork, 2017)
Abstract: This paper introduces the use of new technologies and creative practices in teaching groupwork within two applied Irish postgraduate MA courses (Social Work and Community Development). By reflecting on experiences of teaching groupwork through the use of visual biographies, mask making, aural and video podcasting, the authors argue that creative teaching works to integrate experiential, practical and theoretical knowledge of groupwork. A more widespread adoption and evaluation of creative technologies in teaching groupwork to enhance student learning and affirm professional competencies is proposed. Keywords: social work; community development; creative technologies; podcasting; mask-making; visual biographies; group work; groupwork